SIMULATION OF ELECTRICITY ACCUMULATION PROCESS IN THE COMBINED POWER SYSTEM - Kuznietsov, М.; Melnyk, O.; Smertiuk, V. (Institute of Renewable Energy National Academy of Sciences of Ukraine, 2020)
The purpose of the paper is to develop a model for balancing the processes of electricity generation and consumption for power systems based on renewable energy and using a storage system. Generation modes for wind and especially solar power plants have significant current power gradients, when big changes are possible in a few minutes. When choosing storage systems, it is necessary to take into account such factors as uneven generation and consumption, the amount of possible excess energy or its deficit, the rate of change of power balance and the corresponding speed of batteries charging. The object of research is hybrid power systems with the properties of a local network. Such systems are sensitive to variable generation modes, and the presence of rapid power changes requires analysis of short time intervals. The research method is mathematical modeling of random processes of energy consumption and generation, which allows you to analyze the current balancing of capacities and obtain the integral characteristics of energy storage and reuse. Modeling the operating modes of solar and wind power plants is based on statistical data on weather factors. Then the power balance can be viewed as a superposition of random generation and consumption processes. A feature of the study is taking into account the time gradients of wind and solar power plants, charging speed and status of battery. Analytical research is complicated by the factor of the presence of different processes with special characteristics of the distribution, so a simulation model with an appropriate calculation algorithm is proposed. The proposed energy balance model allows simulating the processes of accumulation and use of energy with different properties of the accumulation system. The results of the study make it possible to compare various configurations of the power system in terms of balance, storage needs and the level of energy losses. This takes into account local and seasonal climatic features. Ref. 21, tab. 1, fig. 2.